A novel self-separating silicon nanowire thin film and application in lithium-ion batteries. (15th February 2023) - Li, Haibin; Kato, Shinya; Ishii, Yosuke; Kurokawa, Yasuyoshi; Soga, Tetsuo
Abstract: Nano silicon structures are important materials for modern electronic devices and have been widely researched with regard to photoelectricity, thermoelectricity, and lithium-ion batteries. However, since the nano silicon structures fabricated by conventional methods cannot be separated from silicon substrates, reuse of the substrate is restricted. Here, we propose a simple fabrication method to separate the nano silicon structures from the silicon substrates, which allows the reuse of the substrates. The fabrication was processed at room temperature, which allows large-area fabrication and is not restricted by the substrate thickness. Honeycomb structures of different length scales observed on both the nano silicon structure and the substrate suggest that the separation occurred due to the amplification of the silicon crystal defects. The nano silicon structures comprised porous silicon with an excellent specific surface area of 480 m 2 g −1 and a mean pore diameter of 5.7 nm. Moreover, the nano silicon structures show good potential as anode materials for lithium-ion batteries wherein the measured reversible capacity was 1, 966 mAh g −1 after 100 cycles. Based on the proposed method and morphological characteristics, the fabricated nano silicon structures can be considered a low-cost material with suitable applications in the energy field.